Looking towards the Forest: Women’s Firewood Consumption and Environmental Degradation in Bayelsa State, Nigeria - Lasisi, Raimi; Alfred, Stephen E.; Collinus, Seibarugu Iyorozitei (Advances in Social Sciences Research Journal, 2015)
The issue of deforestation as a contributory trigger for environmental degradation continues to stay at the centre of global debate on climate change. However, little empirical effort has been directed toward understanding the effect of firewood consumption by rural women and how this contributes to environmental degradation around the world. In the light of this knowledge gap, this paper sets off to show the effect of women’s use of firewood on forest resources and how this contributes to environmental degradation in Bayelsa State and the Niger Delta in general. It asserts that women’s dependence on firewood for domestic and commercial purposes leads to the progressive deterioration of forest resources and by extension environmental degradation. Based on the assumptions of the Materialist Feminist theory, the core argument in this paper is that women in the study area are materially marginalized and as a result, they depend on the natural environment for petite economic survival. As a result, the struggle to raise their income level drives women into putting pressure on forests resources through firewood consumption and this in turn creates conditions that lead to environmental degradation through the loss of biodiversity, increase in carbon emission and sustained flooding. The findings of the study have implications for policy and practice. It is based on these implications that useful suggestions and recommendations are made.